EFISIENSI ADMINISTRASI PERKANTORAN DI KANTOR CAMAT MALALAYANG - ASI ALI, SRI YULAN; Pangkey, Masje Silija; Tulusan, Femmy (Sam Ratulangi University, 2016)
ABSTRACT: The efficiency of the administrative offices at the district office Manado city Malalayangindication has not been effective. Moving on from the problems encountered is the lack of utilization ofhuman resources employee, inadequate facilities and budget are still minimal. The purpose of this studywas to determine how the efficiency of office administration at the sub-district office Malalayang CityResearch using qualitative methods. The informants as many as eight employees in the DistrictGovernment Officials namely Subscript Head, Secretary of Sub district Head, Head of Divisions, 2 Headof Section , and 2 Staff / implementers. Collecting data with interview techniques; while the data wereanalysed using qualitative analysis techniques interactive model of Miles and Hubernann.Based on the results of the study it can be concluded: (1) The efficiency of the administrative officesat sub-district Office Malalayang Manado City are generally good, but not maximum views of the realizationof the achievements of the realization of the budget, the utilization of human resource potential employeesas competence, use of facilities / infrastructure and equipment and supporting facilities, and themechanisms and procedures for the implementation of an office job. (2) Programs and activities of the work/ office administration services that have been defined in the planning of the work / performance at eachfiscal year can generally be carried out and the realization of the results is good / satisfactory, but notoptimally. This means that the use of resources in the implementation of the work / office administrationservices can provide good work / unsatisfactory.Keywords: efficiency, administrative offices.